2015
DOI: 10.1097/scs.0000000000001829
|View full text |Cite
|
Sign up to set email alerts
|

Measuring and Comparing the Cost-Effectiveness of Surgical Care Delivery in Low-Resource Settings

Abstract: Cleft lip and palate (CLP) care is the longest sustained global effort in humanitarian surgical care. However, the relative cost-effectiveness of surgical delivery approaches remains largely unknown. We assessed the cost-effectiveness of two strategies of CLP surgical care delivery in low resource settings: medical mission and comprehensive care center. We evaluated the medical records and costs for 17 India-based medical missions and a Comprehensive Cleft Care Center in Guwahati, India, from Operation Smile, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 19 publications
0
27
0
1
Order By: Relevance
“…Twelve studies (29%) reported on health gains of the mission, reporting heterogeneous methods and outcomes (table 1). Methods used in cleft studies included photographic assessment of aesthetic outcomes,30 69 speech evaluation16 47 or DALYs averted 41 43 48 55. Three cleft studies evaluated speech functionality postoperatively, either by questionnaires61 or speech tests 16 47.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twelve studies (29%) reported on health gains of the mission, reporting heterogeneous methods and outcomes (table 1). Methods used in cleft studies included photographic assessment of aesthetic outcomes,30 69 speech evaluation16 47 or DALYs averted 41 43 48 55. Three cleft studies evaluated speech functionality postoperatively, either by questionnaires61 or speech tests 16 47.…”
Section: Resultsmentioning
confidence: 99%
“…Four cleft studies reported on DALYs averted by cleft lip and palate repair surgery. DALYs averted per patient were 3.9,43 6.041 and 10.1 per patient 48. In three noma missions, a surgeon-reported outcome scale was used to score aesthetic and functional outcome 32 50 52.…”
Section: Resultsmentioning
confidence: 99%
“…Professionals who see only one or two patients a month will not be able to develop the skills they need without good access to this sort of guidance; access to referral centers can also help address the more difficult or treatmentresistant patient presentation [1]. That is the approach used to treat cardiac congenital deformities, cleft palate, and certain kinds of oncologic pathology [2].…”
Section: Corr Insightsmentioning
confidence: 99%
“…The role of surgery in the development of comprehensive healthcare systems and health promotion is therefore increasingly recognized. Importantly, surgical care is also increasingly understood to represent a cost-effective component of primary care in LMICs [ 5 7 ] and could play a critical role in improving multiple domains of healthcare [ 8 ]. Despite such recognition, surgical access remains poor and within many LMICs, the majority of surgical services are largely concentrated in urban centres, leaving rural communities with virtually no access to such care.…”
Section: Introductionmentioning
confidence: 99%